Microeconometric Analysis of Telecommunication Services Market with the use of SARIMA Models - Kaczmarczyk, Paweł (Dynamic Econometric Models, 2017)
The paper presents the results of testing the effectiveness of the multi sectional model in the short-term forecasting of hourly demand for telephone services. The model was based on the integration of the linear regression model with dichotomous independent variables and the SARIMA model. The regression was used as a filter of modelled variability of the demand. The SARIMA was applied to model residual variability. The research shows that the proposed integration provides a greater possibility of approximation and prediction in comparison to the non-supported linear regression model. The results of the study provide support for operational planning of telecommunications operator.